2019
DOI: 10.3171/2018.5.jns172879
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing propranolol as an antitumor agent in von Hippel-Lindau disease

Abstract: OBJECTIVEVon Hippel-Lindau disease (VHL) is a tumor predisposition syndrome characterized by CNS hemangioblastomas (HBs) and clear cell renal cell carcinomas (RCCs) due to hypoxia-inducible factor activation (pseudohypoxia). Because of the lack of effective medical therapies for VHL, HBs and RCCs account for significant morbidity and mortality, ultimately necessitating numerous neurological and renal surgeries. Propranolol is an FDA-approved pan-beta adrenergic antagonist with antitumor effects against infanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 37 publications
3
13
0
Order By: Relevance
“…As shown in Figure 2 B, propranolol ( p = 0.0059) and ICI ( p = 0.0005) significantly decreased the amount of VEGF secreted by 786-O cells. This was also observed in ccRCC with both propranolol ( p = 0.014) and ICI ( p = 0.0028), at variance with the results published by Shepard et al [ 36 ], in which VEGF levels remained unchanged after 200 µM of propranolol treatment. Moreover, we also found a significant reduction of almost 20% in VEGF expression compared to the control, in three independent primary VHL-ccRCCs cultures treated with 100 µM of either propranolol or ICI.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…As shown in Figure 2 B, propranolol ( p = 0.0059) and ICI ( p = 0.0005) significantly decreased the amount of VEGF secreted by 786-O cells. This was also observed in ccRCC with both propranolol ( p = 0.014) and ICI ( p = 0.0028), at variance with the results published by Shepard et al [ 36 ], in which VEGF levels remained unchanged after 200 µM of propranolol treatment. Moreover, we also found a significant reduction of almost 20% in VEGF expression compared to the control, in three independent primary VHL-ccRCCs cultures treated with 100 µM of either propranolol or ICI.…”
Section: Resultssupporting
confidence: 78%
“…Both RCCs share a unique and common characteristic: a homozygous mutation in the VHL gene, which drives the stabilization of HIF protein in the resulting tumors, with HIF-2α being the predominant isoform. [ 36 ]. Hence, targeting HIF might have beneficial antitumor effects in both VHL and RCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although a recent publication supports our hypothesis that propranolol reduces hemangioblastoma growth,23 more studies are needed and with more patients to confirm these results, preferably with fewer previous invasive treatments (such as laser photocoagulation).…”
Section: Discussionsupporting
confidence: 59%
“…In this scenario, where surgery and pharmacological therapies show limited recovery and response for CNS VHL disease, an urgent requirement for new and more effective drugs with reduced side effects for these patients are demanded. www.nature.com/scientificreports www.nature.com/scientificreports/ Some previous studies from Shepard et al and our group have demonstrated that Propranolol, a non-specific β1-and β2-blocker, was efficient on in vitro treatment of CNS Hemangioblastomas primary cultures 19,21,52 . Basically, Propranolol was acting in two ways: i) decreasing cell viability by triggering apoptosis and ii) inhibiting the expression of HIF-dependent targets in VHL HB cells, where HIF-1α degradation is impaired 21 .…”
Section: Discussionmentioning
confidence: 89%